Design, Synthesis, and Targeted Delivery of an Immune Stimulant that Selectively Reactivates Exhausted CAR T Cells. Issue 15 (16th February 2022) - Napoleon, John Victor; Zhang, Boning; Luo, Qian; Srinivasarao, Madduri; Low, Philip S.
Abstract: Although chimeric antigen receptor (CAR) T cells have demonstrated significant promise in suppressing hematopoietic cancers, their applications in treating solid tumors have been limited by onset of CAR T cell exhaustion that accompanies continuous CAR T cell exposure to tumor antigen. To address this limitation, we have exploited the abilities of recently designed universal CARs to bind fluorescein and internalize a fluorescein‐TLR7 agonist conjugate by CAR‐mediated endocytosis. We demonstrate here that anti‐fluorescein CAR‐mediated uptake of a fluorescein‐TLR7‐3 conjugate can reactivate exhausted CAR T cells, leading to dramatic reduction in T cell exhaustion markers (PD‐1 + Tim‐3 + ) and shrinkage of otherwise resistant tumors without inducing systemic activation of the immune system. We conclude that CAR T cell exhaustion can be reversed by administration of a CAR‐targeted TLR7 agonist, thereby enabling the CAR T cells to successfully treat solid tumors without incurring the systemic toxicity that commonly accompanies administration of nontargeted TLR7 agonists. Abstract : Chronic exposure of CAR T cells to tumor antigens can lead to CAR T cell exhaustion and tumor expansion. To reverse this exhaustion, we have developed two orthogonal strategies to target a potent TLR7 agonist specifically to exhausted CAR T cells. We demonstrate here that both strategies rejuvenate exhausted CAR T cells, leading to dramatic reduction in T cell exhaustion markers (PD‐1 + Tim‐3 + ) and shrinkage of CAR T cell resistant tumors.